The Influence of Achievement Motivation and Adversity Quotient on Learning Outcomes in Aqidah Akhlak with Self-Efficacy as a Mediating Variable - Arisah Hanum; Amalia Riski; Namiroh Lubis (Jurnal Ilmu Pendidikan dan Sains Islam Interdisipliner, 2026)
Student participation in school democratic activities is an important aspect of citizenship character development at the elementary school level. Civic Education (PPKn) plays a significant role in instilling democratic values and encouraging students to actively engage in various school activities. This study aims to examine the role of Civic Education in improving elementary school students' participation in school democratic activities. The research employed a literature review method using a qualitative descriptive approach. Data were collected from various relevant sources, including scientific journals, books, and previous studies. The findings indicate that Civic Education enhances student participation through discussions, deliberations, class leader elections, project-based learning, and other democratic activities. Student participation is also supported by a democratic school environment, innovative learning media, digital literacy, parental involvement, and the teacher’s role as a facilitator. In addition to increasing participation, Civic Education helps develop democratic attitudes, responsibility, tolerance, critical thinking skills, and social competencies. Therefore, Civic Education contributes significantly to improving elementary school students’ participation in school democratic activities and supports the development of active, democratic, and responsible citizens.